INVESTIGASI KOROSI BAJA TULANGAN BETON SIRIP DENGAN PROTEKSI KATODIK ARUS TANDING MENGGUNAKAN ANODA MMO-Ti MORTAR KONDUKTIF[Investigation Of Corrosion Of Reinforced Concrete With Impress Current Cathodic Protection Using Mmo-Ti Conductive Mortar Anode] - Anwar, M Syaiful; Nikitasari, Arini; Mabruri, Efendi; Sundjono, Sundjono; Harsisto, Harsisto (Pusat Penelitian Metalurgi dan Material - LIPI, 2014)
INVESTIGASI KOROSI BAJA TULANGAN BETON SIRIP DENGAN PROTEKSI KATODIK ARUSTANDING MENGGUNAKAN ANODA MMO-Ti MORTAR KONDUKTIF. Pada penelitian ini proteksikatodik arus tanding/arus proteksi dengan menggunakan anoda mixed metal oxide-titanium (MMO-Ti) betonkonduktif telah dilakukan terhadap baja tulangan beton baru yang terendam di dalam air laut pada variasi arusproteksi. Tujuan penelitian ini adalah untuk investigasi kinerja arus proteksi untuk mengurangi agresifitaslingkungan di sekitar beton bertulang baru dan untuk mengevaluasi beton bertulang baru setelah diaplikasikanarus proteksi. Proteksi katodik ini bervariasi dilakukan pada arus proteksi 100, 150 dan 200 mA/m² dari luaspenampang baja tulangan. Standar NACE SP0290 digunakan sebagai kriteria standar proteksi katodik ini.Beberapa pengujian untuk melihat pengaruh arus proteksi pada saat catu daya dihidupkan dan dimatikanterhadap sifat korosi baja tulangan beton adalah open circuit potential (OCP) pada saat catu daya dihidupkanselama 3 menit dan kemudian dimatikan selama 4 jam, tafel polarisasi untuk meIn this study, impressed current cathodic protection using MMO-Ti conductive concrete anode was conducted in the new reinforced bar (rebar) concrete submerged in the seawater on the various protecting current. The aim of this study was to investigateperformance of protecting current to reduce aggressive environment in the interface of new rebar cocncrete and also to evaluate new rebar concrete after application of protecting current. This technique was conducted on the various protecting current of 100, 150 and 200 mA/m² by surface area of rebar. NACE SP0290 was used as standard criteria of cathodic protection. Examinations werearried to observe the influent of protecting current at power supply ‘on’ and ‘off’ that was obtained before and after cathodic protection, such as open circuit potential (OCP) at switch ‘on’ up to 3 minutes and then switch ‘off’ up to 4 hours, tafel polarisation to record corrosion potential, polarisation resistant, corrosion rate at initial and after application of protecting current. Cyclic polarisation test was performed to know susceptibility of pitting corrosion on the rebar concrete. The resultshowed that this techniquehave been successfullyapplied and have been meet standard criteria of NACE SP02090. Their corrosion potential of rebar concrete obtained after 4 hours of switch ‘off’ lower as well as corrosion rate compared to sample without protecting current (PPC 1) during 30 days submerged in the seawater. Pitting corrosion not found in the all of samples.02090. Potensial korosi bajatulangan beton yang ditentukan setelah 4 jam dari arus proteksi dimatikan menghasilkan nilai potensialterendah/paling negatif dan nilai laju korosi lebih rendah dari pada benda uji tanpa arus proteksi (PPC 1) selama30 hari perendaman dan tanpa terjadinya korosi sumuran (pitting). AbstractIn this study, impressed current cathodic protection using MMO-Ti conductive concrete anode was conducted in the new reinforced bar (rebar) concrete submerged in the seawater on the various protecting current. The aim of this study was to investigateperformance of protecting current to reduce aggressive environment in the interface of new rebar cocncrete and also to evaluate new rebar concrete after application of protecting current. This technique was conducted on the various protecting current of 100, 150 and 200 mA/m² by surface area of rebar. NACE SP0290 was used as standard criteria of cathodic protection. Examinations werearried to observe the influent of protecting current at power supply ‘on’ and ‘off’ that was obtained before and after cathodic protection, such as open circuit potential (OCP) at switch ‘on’ up to 3 minutes and then switch ‘off’ up to 4 hours, tafel polarisation to record corrosion potential, polarisation resistant, corrosion rate at initial and after application of protecting current. Cyclic polarisation test was performed to know susceptibility of pitting corrosion on the rebar concrete. The resultshowed that this techniquehave been successfullyapplied and have been meet standard criteria of NACE SP02090. Their corrosion potential of rebar concrete obtained after 4 hours of switch ‘off’ lower as well as corrosion rate compared to sample without protecting current (PPC 1) during 30 days submerged in the seawater. Pitting corrosion not found in the all of samples.